Proactive Personality and Employee Creativity: A Moderated Mediation Model of Multisource Information Exchange and LMX - Zhang, Aishi; Li, Xi; Guo, Yuchen (Frontiers in Psychology, 2021)
Integrating the social perspective of creativity and the goal-regulatory process perspective of proactivity, this study investigates how proactive personality influences two forms of employee creativity-incremental creativity and radical creativity through multisource information exchange. Using a moderated mediation framework, this study suggests that LMX moderates the positive association between proactive personality and those two forms of employee creativity. The results of this study, drawn from the sample of 500 employees and their immediate supervisors in a large state-owned company of China, support most of the hypotheses. Theoretical and practical implications of the findings, as well as the limitations of this study and the directions for future research, are discussed.